2021
DOI: 10.3390/ma14092464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Residual Trace Amounts of Fe and Al in Li[Ni1/3Mn1/3Co1/3]O2 Cathode Active Material for the Sustainable Recycling of Lithium-Ion Batteries

Abstract: As the explosive growth of the electric vehicle market leads to an increase in spent lithium-ion batteries (LIBs), the disposal of LIBs has also made headlines. In this study, we synthesized the cathode active materials Li[Ni1/3Mn1/3Co1/3]O2 (NMC) and Li[Ni1/3Mn1/3Co1/3Fe0.0005Al0.0005]O2 (NMCFA) via hydroxide co-precipitation and calcination processes, which simulate the resynthesis of NMC in leachate containing trace amounts of iron and aluminum from spent LIBs. The effects of iron and aluminum on the physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
(47 reference statements)
1
5
1
Order By: Relevance
“…Noticeably, the first semicircles in a high frequency region that are related to the film resistance induced by the formation of solid electrolyte interphase (SEI) between electrodes and electrolytes gradually shrank with an increased cycle number from 10 to 50 in both samples (see the insets in the figures). It is hard to intuitively interpret the abnormal phenomenon about the gradual decrease of film resistance, which is contrary to other relevant research [30,31]. In the meantime, the second semicircles in a low frequency region regarding charge transfer resistance (R ct ) indicated incremental trends in both samples during cycling due to the structural degradation of the cathode active materials.…”
Section: Resultscontrasting
confidence: 63%
“…Noticeably, the first semicircles in a high frequency region that are related to the film resistance induced by the formation of solid electrolyte interphase (SEI) between electrodes and electrolytes gradually shrank with an increased cycle number from 10 to 50 in both samples (see the insets in the figures). It is hard to intuitively interpret the abnormal phenomenon about the gradual decrease of film resistance, which is contrary to other relevant research [30,31]. In the meantime, the second semicircles in a low frequency region regarding charge transfer resistance (R ct ) indicated incremental trends in both samples during cycling due to the structural degradation of the cathode active materials.…”
Section: Resultscontrasting
confidence: 63%
“…It is therefore possible that Al 3+ substitutes Ni 3+ and Co 3+ . Also, since the ionic radii of Ni 3+ (0.56 Å), Co 3+ (0.545 Å), and Mn 4+ (0.54 Å) are close to that of Al 3+ (0.53 Å), substitution may occur [36,37]. Due to a large difference in ionic radii between Al 3+ (0.53 Å), Li + (0.76 Å, 3a) and Ni 2+ (0.69 Å), the substitution in these cases cannot occur.…”
Section: Resultsmentioning
confidence: 99%
“…Also, since the ionic radii of Ni 3+ (0.56 Å), Co 3+ (0.545 Å), and Mn 4+ (0.54 Å) are close to that of Al 3+ (0.53 Å), substitution may occur. 36,37 Due to a large difference in ionic radii between Al 3+ (0.53 Å), Li + (0.76 Å, 3a) and Ni 2+ (0.69 Å), the substitution in these cases cannot occur. Refinement of the occupancy factor also confirms this hypothesis since the occupation of Co, Mn, and Ni is reduced, which means that they have been substituted by another element, in this case Al 3+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In our previous study, it was confirmed that various metal and nonmetal impurities are present in the regenerated cathode active materials after the purification process. 17 In addition, the effects of relatively high concentrations of impurities such as Fe, 18,19 Al 20,21 Cu, 22 and Na 23 on the resynthesized cathode active materials were investigated individually at impurity levels. However, Zn and Ca have been overlooked in related studies on impurity effects because of their negligible concentration.…”
Section: Introductionmentioning
confidence: 99%